2021
DOI: 10.1088/1361-6463/abf807
|View full text |Cite
|
Sign up to set email alerts
|

Passivation of thermally-induced defects with hydrogen in float-zone silicon

Abstract: In this study, passivation of thermally-activated recombination centers with hydrogen in n-type float zone (FZ) Si containing nitrogen has been investigated. Prior to hydrogenation samples were heated to 550 °C using rapid thermal annealing and conventional furnaces. A large decrease in minority carrier lifetime occurred upon the heat-treatments confirming previous reports. A sequence of electron traps created in this process have been detected in the deep level transient spectra and characterized. Significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 29 publications
(64 reference statements)
2
4
0
Order By: Relevance
“…The values of ΔE for E1 and E2 matched previous. [19][20][21][22][23] The values of σ app were within the range of previous DLTS studies with magnitudes of 10 −15 -10 −16 cm 2 . [20][21][22][23] The other candidates for origins of E1 and E2 in Cz-Si are VV, VO 2 * , V 2 O, and VO.…”
Section: Resultssupporting
confidence: 84%
See 2 more Smart Citations
“…The values of ΔE for E1 and E2 matched previous. [19][20][21][22][23] The values of σ app were within the range of previous DLTS studies with magnitudes of 10 −15 -10 −16 cm 2 . [20][21][22][23] The other candidates for origins of E1 and E2 in Cz-Si are VV, VO 2 * , V 2 O, and VO.…”
Section: Resultssupporting
confidence: 84%
“…[19][20][21][22][23] The values of σ app were within the range of previous DLTS studies with magnitudes of 10 −15 -10 −16 cm 2 . [20][21][22][23] The other candidates for origins of E1 and E2 in Cz-Si are VV, VO 2 * , V 2 O, and VO. 27,28) However, the activation energies obtained in DLTS evaluations are 0.23 and 0.43 eV for VV, 0.06 eV for VO 2 * , and 0.23 and 0.47 eV for V 2 O; therefore, they do not seem to be the origins of E1 and E2.…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…[1,2] It has been found that hydrogen enhances the mitigation or deactivation of boron-oxygen defects responsible for the light-induced degradation in Czochralski-grown (Cz) Si solar cells and can passivate detrimental transition metal impurities, dislocation clusters, and thermally induced defects. [1][2][3][4][5] On the contrary, it has been suggested that hydrogen is responsible for the so-called light and elevated temperature-induced degradation (LeTID), which can produce a degradation of efficiency of solar cells between 2.5% and 16% relative and is most significant in multicrystalline Si passivated emitter and rear cells (PERC). [6][7][8][9] In most of the technologically important cases, the details of interaction of hydrogen atoms with other lattice defects are not well understood.…”
Section: Introductionmentioning
confidence: 99%
“…[1] The addition of nitrogen gives rise to a family of defects which appear after heat treatment in the temperature range of 450-700 °C, and these defects lead to a strong decrease in minority carrier lifetime due to the origin of defect levels within the electronic bandgap. [2][3][4][5][6][7] There are numerous studies of these defect levels via deep-level transient spectroscopy (DLTS), [2][3][4][5][6][7][8][9][10] which typically identify the defect levels by their activation energy, but the microscopic origin of the defects is much less understood. Nonetheless, some studies [7,10] suggest that an electron trap residing around 0.34 eV below the conduction band corresponds to a nitrogen-vacancy (NV) pair, which matches closely with the reported value of 0.33 AE 0.02 eV for the off-center substitutional nitrogen atom as determined by electron paramagnetic resonance (EPR) spectroscopy.…”
Section: Introductionmentioning
confidence: 99%